Kinorhyncha from the Iberian Peninsula: new data from the first intensive sampling campaigns - Sánchez, Nuria; Herranz, María; Benito, Jesús; Pardos, Fernando (Zootaxa, 2012)
Data are presented from the first intensive sampling of Kinorhyncha around the Iberian Peninsula over a 21-year periodfrom 1990 to 2011, from 81 sites mostly in less than 100 m water depth. Light-microscopic examination of approximately2000 specimens yielded 11 genera and 29 species, only 11 of which were previously recorded from peninsular waters. Thebalance comprises ten new species records for the peninsula and eight new species that are yet to be described. The mostspeciose genus is Echinoderes, with ten species, two of them new, followed by Pycnophyes (nine species, three new).There are two species of Antygomonas (one new), and one each for the genera Campyloderes, Centroderes, Condyloderes(one new), Dracoderes, Meristoderes, Semnoderes, Kinorhynchus (one new), and Paracentrophyes. The most ubiquitousspecies in the samples, appearing at nearly all localities was Pycnophyes dentatus, newly recorded for the Iberian Penin-sula and found at nearly all sampled localities and in high numbers. Echinoderes cantabricus, E. hispanicus and E. dujar-dinii also have a wide distribution along both Atlantic and Mediterranean coasts. Known information on diversity, biogeography and ecology (depth, sediment and abundance) is discussed.